Concerns on Little League Elbow - Wells, Michael J. (1995)
Little League elbow is a common overuse injury that will become more prevalent as more youths participate in baseball programs and other sports that involve overhead arm activities. The condition is highly treatable if diagnosed early in its development. Symptoms such as swelling and limited range of motion usually indicate an advanced overuse condition. Prevention and treatment should emphasize education of athletes, parents, and coaches about coaches about its etiology. Factors involved are proper pitching mechanics, stretching and strengthening programs, improving early recognition, and, most importantly, limiting the number of pitches thrown daily.